Reinforced embankment constructed along irrigation canal - Teerachavalvong, Kritsada; Kaipinit, Surasak; Suksawat, Taweephong; Saiprasertkij , Kawin (Thai Geoscience Journal, 2020)
The Department of Rural Roads has reconstructed the asphalt concrete road during April to May 2016, KS.4064 that is along the Right Main Canal (RMC) of the Lam Pao Dam in Yang Talat district, Kalasin province, the northeast region of Thailand. The distance of road is 1.60km, approximately. During construction, the road embankment collapsed about 300 meters after the asphaltic concrete was paved. This paper focuses on the stability of reinforced road embankment on the KS.4064 by using geogrids and soil replacement methods in order to reinforce the embankment. The PLAXIS 2D software is used to analyze the Factor of Safety of the reinforced road embankment. The required minimum Factor of Safety of 1.30 for the rapid drawdown condition is considered as the criteria for this project. The results from simulations demonstrated 1.563 and 1.640 for geogrid reinforcement and soil replacement methods which indicates that the stability of slope is adequate even though the worst-case condition is considered.